Novel chemically amplified positive photoresist compositions and preparation thereof
By using a mixture of acetoxystyrene and hydroxystyrene copolymers as photoresist, the problems of complex preparation and unstable composition in the prior art are solved, and the photolithography performance is improved and the line width roughness is achieved. Significantly reduced.
Patent Information
- Application Number
- CN202310692140.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-06-12
AI Technical Summary
The preparation of existing chemically amplified positive photoresist compositions is complex and difficult to control, resulting in unstable polymer composition and affecting photolithography performance.
Using a mixture of acetoxystyrene copolymer and hydroxystyrene copolymer as photoresist, the formation of a simple structure and easy to prepare by adjusting the content of each copolymer and introducing photoacid generator groups on the main chain. novel photoresist compositions.
Accurate control of polymer composition is achieved, and the lithographic performance, especially the reduction of line width roughness (LWR), is improved, to achieve a reduction effect of greater than 40%, preferably greater than 50%, preferably greater than 60%.
Smart Images

Figure CN119126491A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to novel polymers and compositions containing the same, thereby providing polymer-based photoresists for various applications in photolithography such as KrF. The photoresist composition of the present invention comprises a mixture of an acetoxystyrene copolymer and a hydroxystyrene copolymer. Background Art
[0002] Chemically amplified positive photoresist compositions generally contain a resin binder, a photoacid generator (PAG), a base called a quencher, additives, and a solvent(s). Prior art such as IBM's U.S. Patent No. 6,365,321, U.S. Patent No. 4,491,628, U.S. Patent No. 7,951,525, and Shin-Etsu Chemical Co.'s U.S. Patent No. 5,356,753, U.S. Patent No. 5,731,126, and Hitachi's U.S. Patent No. 4,745,169, and TOK's U.S. Patent No. 6,074,962, U.S. Patent No. 5,990,338, U.S. Patent No. 6,749,991, U.S. Patent No. 6,897,012 and JSR's U.S. Patent No. 5,332,650, U.S. Patent No. 6,846,895, U.S. Patent No. 7,041,748, and FujiFilm's U.S. Patent No. 6,376,152, U.S. Patent No. 6,485,883, U.S. Patent No. 6,537,718, U.S. Patent No. 6,103,449 and Hyundai Electronics, U.S. Patent No. 6,589,707, Hitachi U.S. Patent No. 7,659,047, Fujitsu Ltd. U.S. Patent No. 6,027,856, and Samsung Electronic Company U.S. Patent No. 6,872,502. In addition, the following prior art teaches Shipley Chemical Co. U.S. Patent No. 7,211,365, U.S. Patent No. 6,048,672, U.S. Patent No. 6,800,422, U.S. Patent No. 6,136,501, U.S. Patent No. , U.S. Patent No. , U.S. Patent No. , U.S. Patent No. , U.S. Patent No. , U.S. Patent No. , Sumitomo Chemical Company U.S. Patent No. 5,800,966, U.S. Patent No. 6,153,349, TOK U.S. Patent No. 6340553, U.S. Patent No. 9,459,528, U.S. Patent No. 6,815,144, U.S. Patent No. 7,172,848, U.S. Patent No. 7,364,831, Clariant U.S. Patent No. 6,576,394 and Kempur Microelectronics, Inc. U.S. Patent No. 9,766,542.
[0003] These copolymers, made from three or more different monomers, are structurally complex and their reproducible preparation is extremely challenging. As a result, control of the batch-to-batch preparation of the polymers is very difficult, making control of the polymer composition almost impossible.
[0004] There is still a need in the art to obtain a novel chemically amplified positive photoresist composition comprising a copolymer that is simple in structure and easy to prepare, and at the same time, the novel chemically amplified positive photoresist composition can achieve improved lithographic performance. Summary of the invention
[0005] The present invention relates to a mixture of two copolymers which are simple in structure and easy to prepare. The chemical structures of the two copolymers are very similar, and therefore their mixture is homogeneous without phase separation.
[0006] Additionally, by adjusting the content of each copolymer in the mixture and by introducing photoacid generator groups on the main chain of the copolymer, desired properties required for enhanced lithographic performance can be obtained.
[0007] The present invention relates to a novel chemically amplified positive photoresist composition, comprising a mixture of two copolymers of a copolymer (A) and a copolymer (B), wherein:
[0008] Copolymer (A) is an acetoxystyrene copolymer having a dissolution inhibiting acetoxy group, a pendant photoacid generator group and a photoacid dissociable group, wherein copolymer (A) contains equal to or greater than 60 mol%, preferably 70 mol% to 80 mol%, of an aromatic-containing group based on the total moles of the monomers; and
[0009] Copolymer (B) is a hydroxystyrene copolymer having alkali-soluble hydroxyl groups and photoacid-dissociable groups, wherein copolymer (B) contains equal to or greater than 60 mol%, preferably 70 mol% to 80 mol%, of aromatic-containing groups based on the total moles of monomers.
[0010] The aromatic group contained in the copolymer (A) and the copolymer (B) refers to a group containing an aromatic group. Preferably, the aromatic group contained in the copolymer (A) and the copolymer (B) is selected from the following: phenyl, biphenyl, naphthalene and the like.
[0011] The content of copolymer (A) is preferably in the range of 30-70 wt %, such as 30, 40, 50, 60 and 70 wt %, based on the total weight of the mixture of the two copolymers of copolymer (A) and copolymer (B).
[0012] The content of copolymer (B) is preferably in the range of 30 wt% to 70 wt%, such as 30 wt%, 40 wt%, 50 wt%, 60 wt% and 70 wt%, based on the total weight of the mixture of the two copolymers of copolymer (A) and copolymer (B).
[0013] The photoacid dissociable groups contained in the copolymer (A) and the copolymer (B) are selected from the following: alkyl ester groups, alicyclic ester groups, or combinations thereof;
[0014] Preferably, the photoacid-dissociable group is a (meth)acrylate group, which means a methacrylate group or an acrylate group.
[0015] Preferably, the photoacid-dissociable group is selected from the following: an alkyl (meth)acrylate group, an alicyclic (meth)acrylate group, or a combination thereof.
[0016] Preferably, the photoacid cleavable group is an alkyl (meth)acrylate group, wherein the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl.
[0017] Preferably, the photoacid-dissociable group is a tert-butyl (meth)acrylate group.
[0018] Preferably, the photoacid-dissociable group is an alicyclic (meth)acrylate group selected from a 1-alkyl-1-cycloalkyl (meth)acrylate group and a 2-alkyl-2-adamantyl (meth)acrylate group.
[0019] Preferably, the photoacid cleavable group is a 1-alkyl-1-cycloalkyl (meth)acrylate group, wherein the alkyl group is selected from the following: methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl; and the cycloalkyl group is selected from the following: cyclopentyl, cyclohexyl and cycloheptyl.
[0020] Preferably, the photoacid cleavable group is a 2-alkyl-2-adamantyl (meth)acrylate group, wherein the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl.
[0021] Preferably, the photoacid-dissociable group is a combination of a 1-alkyl-1-cycloalkyl(meth)acrylate group and / or a 2-alkyl-2-adamantyl(meth)acrylate group and / or a tert-butyl(meth)acrylate group.
[0022] The side chain photoacid generator group contained in the copolymer (A) is a 2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium group.
[0023] Copolymer (A)
[0024] The copolymer (A) is a random copolymer, and it may be a binary copolymer, a ternary copolymer, or a tetraary copolymer.
[0025] The copolymer (A) is prepared by copolymerization of acetoxystyrene monomer, 2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium monomer and one or more other comonomers.
[0026] The one or more other comonomers are selected from (meth)acrylate monomers. (Meth)acrylate monomers refer to methacrylate monomers or acrylate monomers.
[0027] Based on the total moles of monomers of copolymer (A), the preferred range of acetoxystyrene monomer is 60 mol%-90 mol%, for example 60 mol%, 65 mol%, 70 mol%, 75 mol%, 80 mol%, 85 mol%, 90 mol%, etc.
[0028] The mol% content of the aromatic group-containing copolymer (A) is equal to the mol% content of the acetoxystyrene monomer based on the total moles of the monomers of the copolymer (A).
[0029] The preferred range of the (meth)acrylate monomer is 10 mol% to 30 mol%, for example, 10 mol%, 15 mol%, 20 mol%, 25 mol%, 30 mol%, etc., based on the total moles of the monomers of the copolymer (A).
[0030] The preferred range of the triphenylsulfonium 2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonate monomer is 5 mol% to 20 mol%, for example 5 mol%, 10 mol%, 15 mol%, 20 mol%, etc., based on the total moles of the monomers of the copolymer (A).
[0031] The (meth)acrylate monomer is selected from the group consisting of an alkyl (meth)acrylate monomer, an alicyclic (meth)acrylate monomer, or a combination thereof.
[0032] With respect to the alkyl (meth)acrylate monomer, the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, and isopentyl.
[0033] Preferably, the alkyl (meth)acrylate monomer is tert-butyl (meth)acrylate monomer.
[0034] The alicyclic (meth)acrylate monomer is selected from 1-alkyl-1-cycloalkyl (meth)acrylate monomers and 2-alkyl-2-adamantyl (meth)acrylate monomers.
[0035] With respect to the 1-alkyl-1-cycloalkyl (meth)acrylate group, the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl; and the cycloalkyl group is selected from the group consisting of cyclopentyl, cyclohexyl and cycloheptyl.
[0036] With respect to the 2-alkyl-2-adamantyl (meth)acrylate monomer, the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, and isopentyl.
[0037] Alternatively, the (meth)acrylate monomer is a combination of a 1-alkyl-1-cycloalkyl (meth)acrylate monomer and / or a 2-alkyl-2-adamantyl (meth)acrylate monomer and / or a tert-butyl (meth)acrylate monomer.
[0038] The preparation method of copolymer (A) is well known in the art. Typically, copolymer (A) is prepared by free radical polymerization of acetoxystyrene monomer, 2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium monomer and one or more comonomers in the presence of a free radical initiator. Preferably, the free radical initiator is AIBN (azobisisobutyronitrile).
[0039] The weight average molecular weight (Mw) of the copolymer (A) is 5,000-25,000 Daltons. Preferably, the weight average molecular weight (Mw) of the copolymer (A) is 8,000-15,000 Daltons.
[0040] The weight average molecular weight (Mw) of the copolymer (A) is measured by GPC (gel permeation chromatography).
[0041] GPC (gel permeation chromatography) is used for weight average molecular weight (Mw) determination. The GPC system uses an HPLC isocratic pump, an autosampler, an RI (refractive index) detector, and a micro-styrogel column. Monodisperse standards of polystyrene are used to generate a calibration graph for evaluating the Mw of unknown samples.
[0042] The polydispersity of copolymer (A) is 1.2-4.0. Preferably, the polydispersity of copolymer (A) is 1.2 to 2.5.
[0043] Copolymer (B)
[0044] The copolymer (B) is a random copolymer, and it may be a binary copolymer, a ternary copolymer, or a tetraary copolymer.
[0045] The preparation method of copolymer (B) is well known in the art. Generally, copolymer (B) is prepared by saponifying a copolymer of acetoxystyrene monomer and one or more (meth)acrylate monomers using a base in a non-aqueous solvent, wherein the (meth)acrylate monomer is as described above.
[0046] Preferably, the base may be ammonium hydroxide. Preferably, the non-aqueous solvent may be methanol.
[0047] Copolymer (B) is a hydroxystyrene copolymer having alkali-soluble hydroxyl groups and photoacid-dissociable groups, wherein copolymer (B) contains equal to or greater than 60 mol%, preferably 70 mol% to 80 mol%, of aromatic-containing groups based on the total moles of monomers.
[0048] The copolymer (B) is composed of a monomer unit containing an alkali-soluble hydroxyl group and a monomer unit containing a photoacid-dissociable group.
[0049] Based on the total molar number of monomers of copolymer (B), the preferred range of monomer units containing alkali-soluble hydroxyl groups is 70 mol%-80 mol%, for example 70 mol%, 71 mol%, 72 mol%, 73 mol%, 74 mol%, 75 mol%, 76 mol%, 77 mol%, 78 mol%, 79 mol%, 80 mol% and the like.
[0050] Based on the total moles of the monomers of the copolymer (B), the preferred range of monomer units containing photoacid-dissociable groups is 20 mol%-30 mol%, for example 20 mol%, 21 mol%, 22 mol%, 23 mol%, 24 mol%, 25 mol%, 26 mol%, 27 mol%, 28 mol%, 29 mol%, 30 mol% and the like.
[0051] The mol% content of the aromatic group-containing copolymer (B) is equal to the mol% content of the monomer unit containing an alkali-soluble hydroxyl group based on the total moles of the monomers of the copolymer (B).
[0052] The weight average molecular weight (Mw) of the copolymer (B) is 5,000-25,000 Daltons. Preferably, the weight average molecular weight (Mw) of the copolymer (B) is 8,000-15,000 Daltons.
[0053] The weight average molecular weight (Mw) of the copolymer (B) is measured by GPC (gel permeation chromatography).
[0054] GPC (Gel Permeation Chromatography) is used for weight average molecular weight (Mw) determination. The GPC system uses an HPLC constant flow pump, an autosampler, an RI (refractive index) detector, and a micro polystyrene gel column. Monodisperse standards of polystyrene are used to generate a calibration graph for evaluating the Mw of unknown samples.
[0055] The polydispersity of copolymer (B) is 1.2-4.0. Preferably, the polydispersity of copolymer (B) is 1.2 to 2.5.
[0056] The present invention relates to a novel chemically amplified positive photoresist composition, comprising:
[0057] (a) a mixture of two copolymers of copolymer (A) and copolymer (B), wherein copolymer (A) and copolymer (B) are as defined above;
[0058] (b) a solvent or a mixture of solvents;
[0059] (c) a base as a quencher; and
[0060] (d) Optionally, a surfactant.
[0061] Based on the total weight of the novel chemically amplified positive photoresist composition, the preferred content range of the above component (a) (a mixture of two copolymers of copolymer (A) and copolymer (B)) is 5 wt %-30 wt %, for example, 5 wt %, 10 wt %, 15 wt %, 20 wt %, 25 wt %, 30 wt %, etc.
[0062] Based on the total weight of the novel chemically amplified positive photoresist composition, the preferred content range of the above component (b) (solvent or solvent mixture) is 65 wt %-95 wt %, for example, 65 wt %, 70 wt %, 75 wt %, 80 wt %, 85 wt %, 90 wt % and 95 wt %, etc.
[0063] Based on the total weight of the novel chemically amplified positive photoresist composition, the preferred content range of the above component (c) (base as a quencher) is 0.1 wt%-5 wt%, for example, 0.1 wt%, 0.5 wt%, 1.0 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4.0 wt%, 4.5 wt%, 5 wt%, etc.
[0064] If present, component (d) (optionally, surfactant) is preferably present in an amount ranging from 0.1 wt % to 2.0 wt %, such as 0.1 wt %, 0.5 wt %, 1.0 wt %, 1.5 wt %, 2.0 wt %, etc., based on the total weight of the chemically amplified positive photoresist composition.
[0065] The solvent of the chemically amplified positive photoresist composition may be selected from the following: ethyl lactate, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, cyclohexanone, cyclopentanone, 2-methylcyclohexanone, 2-heptanone, propylene carbonate, γ-butyrolactone and mixtures thereof.
[0066] The base of the chemically amplified positive photoresist composition may be an organic base, such as an amine or an ammonium salt.
[0067] The surfactant may be selected from silicone polymers having pendant polyether groups such as XIAMETER TM OFX-3667, XIAMETER TM OFX-0190、DOWSIL TM OFX-0400, XIAMETER TM OFX-5098、VORASURF TM DC 5103, XIAMETER TM OFX-5220、DOWSIL TM OFX-5247、DOWSIL TM OFX-5329, XIAMETER TM OFX-5330、SYLGARD TM OFX-0309, XIAMETER TM OFX-5211、VORASURF TM TF 5067, Silsurf A004, SilsurfA008, Silsurf A010, Silsurf C208, Silsurf D208, Silsurf D212, Silwet L 7604, SilwetL 7608, Silwet L 7609, Silwet L 408, Silwet L 618, Silwet L 625.
[0068] Variation of the content of copolymer (A) and copolymer (B) in the mixture will provide precise control of the polymer composition and address the challenging control of polymer composition by the polymerization process.
[0069] Additionally, the presence of pendant photoacid generator groups on the backbone of the copolymer structure enhances the lithographic properties of the photoresist.
[0070] The photoresist composition of the present invention can achieve a % reduction in line width roughness (LWR) of greater than 40%, preferably greater than 50%, preferably greater than 60%, preferably greater than 70%.
[0071] Description of the drawings
[0072] Figure 1 Shown is a comparison of line width roughness (LWR) values of AxBx (photoresist composition of the invention) and Bx (control photoresist) using a scanning electron microscope (SEM) of a "line and space mode" with a line width of 450 nm. Example
[0073] The following examples illustrate the technical solutions of the present invention and are not intended to limit the scope of the invention.
[0074] Example 1: Synthesis of copolymer A1
[0075] Poly(4-acetoxystyrene-co-tert-butyl methacrylate-co-2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium) (75 / 20 / 5, molar ratio) (aromatic group content: 75 mol%): 81.0 g (0.5 mol) of 4-acetoxystyrene, 18.96 g (0.133 mol) of tert-butyl methacrylate, 19.22 g (0.033 mol) of 2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml THF and added dropwise to 2.5 liters of DI water with stirring. The precipitated polymer was filtered, rinsed with water 1.0 L and dried under vacuum at 50° C. to give a white powder (Mw=13,800 and Mw / Mn=2.1).
[0076] Example 2: Synthesis of Copolymer A2
[0077] Poly(4-acetoxystyrene-co-tert-butyl methacrylate-co-2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium) (73 / 20 / 7, molar ratio) (aromatic group content: 73 mol%): 81.0 g (0.5 mol) of 4-acetoxystyrene, 19.48 g (0.137 mol) of tert-butyl methacrylate, 27.64 g (0.048 mol) of 2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml THF and added dropwise to 2.5 liters of DI water with stirring. The precipitated polymer was filtered, rinsed with water 1.0 L and dried under vacuum at 50° C. to give a white powder (Mw=12,000 and Mw / Mn=2.13).
[0078] Example 3: Synthesis of Copolymer A3
[0079] Poly(4-acetoxystyrene-co-tert-butyl methacrylate-co-2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium) (70 / 25 / 5, molar ratio) (aromatic group content: 70 mol%): 81.0 g (0.5 mol) of 4-acetoxystyrene, 25.39 g (0.179 mol) of tert-butyl methacrylate, 20.59 g (0.036 mol) of 2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml THF and added dropwise to 2.5 liters of DI water with stirring. The precipitated polymer was filtered, rinsed with water 1.0 L and dried under vacuum at 50° C. to give a white powder (Mw=13,850 and Mw / Mn=1.59).
[0080] Example 4: Synthesis of Copolymer A4
[0081] Poly(4-acetoxystyrene-co-2-methyl-2-adamantyl methacrylate-co-2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium) (65 / 25 / 10, molar ratio) (aromatic group content: 65 mol%): 81.0 g (0.5 mol) of 4-acetoxystyrene, 45.03 g (0.192 mol) of 2-methyl-2-adamantyl methacrylate, 44.35 g (0.077 mol) of 2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml THF and added dropwise to 2.5 liters of DI water with stirring. The precipitated polymer was filtered, rinsed with water 1.0 L and dried under vacuum at 50° C. to give a white powder (Mw=12,700 and Mw / Mn=2.44).
[0082] Example 5: Synthesis of Copolymer A5
[0083] Poly(4-acetoxystyrene-co-2-methyl-2-adamantyl methacrylate-co-2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium) (70 / 25 / 5, molar ratio) (aromatic group content: 70 mol%): 81.0 g (0.5 mol) of 4-acetoxystyrene, 41.81 g (0.179 mol) of 2-methyl-2-adamantyl methacrylate, 20.59 g (0.036 mol) of 2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml THF and added dropwise to 2.5 liters of DI water with stirring. The precipitated polymer was filtered, rinsed with water 1.0 L and dried under vacuum at 50° C. to give a white powder (Mw=13,780 and Mw / Mn=1.7).
[0084] Example 6: Synthesis of Copolymer A6
[0085] Poly(4-acetoxystyrene-co-2-methyl-2-adamantyl methacrylate-co-2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium) (75 / 20 / 5, molar ratio) (aromatic group content: 75 mol%): 81.0 g (0.5 mol) of 4-acetoxystyrene, 31.22 g (0.133 mol) of 2-methyl-2-adamantyl methacrylate, 19.22 g (0.033 mol) of 2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml THF and added dropwise to 2.5 liters of DI water with stirring. The precipitated polymer was filtered, rinsed with water 1.0 L and dried under vacuum at 50° C. to give a white powder (Mw=13,650 and Mw / Mn=1.38).
[0086] Example 7: Synthesis of Copolymer A7
[0087] Poly(4-acetoxystyrene-co-tert-butyl methacrylate-co-2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium) (60 / 20 / 20, molar ratio) (aromatic group content: 60 mol%): 60.75 g (0.375 mol) of 4-acetoxystyrene, 17.78 g (0.125 mol) of tert-butyl methacrylate, 72.07 g (0.125 mol) of 2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml THF and added dropwise to 2.5 liters of DI water with stirring. The precipitated polymer was filtered, rinsed with water 1.0 L and dried under vacuum at 50° C. to give a white powder (Mw=14,810 and Mw / Mn=1.8).
[0088] Example 8: Synthesis of Copolymer A8
[0089] Poly(4-acetoxystyrene-co-tert-butyl methacrylate-co-2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium) (60 / 25 / 15, molar ratio) (aromatic group content: 60 mol%): 60.75 g (0.375 mol) of 4-acetoxystyrene, 36.64 g (0.156 mol) of tert-butyl methacrylate, 54.05 g (0.094 mol) of 2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml THF and added dropwise to 2.5 liters of DI water with stirring. The precipitated polymer was filtered, rinsed with water 1.0 L and dried under vacuum at 50° C. to give a white powder (Mw=13,310 and Mw / Mn=1.34).
[0090] Example 9: Synthesis of Copolymer B1
[0091] Poly(4-hydroxystyrene-co-tert-butyl methacrylate) (80 / 20, molar ratio) (aromatic group content: 80 mol%): Step 1 - 81.0 g (0.5 mol) of 4-acetoxystyrene, 17.75 g (0.125 mol) of tert-butyl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried under vacuum at 50° C. to produce a white powder (Mw=15,000 and Mw / Mn=2.1). Step 2 - 10 grams of the copolymer from step 1, 20 grams of ammonium hydroxide (28-30%) and 100 mL of methanol were heated at 65°C with stirring for 18 h. The resulting solution was precipitated in 500 mL of HCl solution (5%). After stirring for 30 min, the resulting powder was filtered. Rinse with 150 mL of water and dry under vacuum at 50°C to provide a white powder (Mw=13,000 and Mw / Mn=1.9).
[0092] Example 10: Synthesis of Copolymer B2
[0093] Poly(4-hydroxystyrene-co-tert-butyl methacrylate) (75 / 25, molar ratio) (aromatic group content: 75 mol%): Step 1 - 81.0 g (0.5 mol) of 4-acetoxystyrene, 23.71 g (0.167 mol) of tert-butyl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried under vacuum at 50° C. to produce a white powder (Mw=14,000 and Mw / Mn=2.23). Step 2 - 10 grams of the copolymer from step 1, 20 grams of ammonium hydroxide (28-30%) and 100 mL of methanol were heated at 65°C with stirring for 18 h. The resulting solution was precipitated in 500 mL of HCl solution (5%). After stirring for 30 min, the resulting powder was filtered. Rinse with 150 mL of water and dry under vacuum at 50°C to provide a white powder (Mw = 11,700 and Mw / Mn = 1.95).
[0094] Example 11: Synthesis of Copolymer B3
[0095] Poly(4-hydroxystyrene-co-tert-butyl methacrylate) (70 / 30, molar ratio) (aromatic group content: 70 mol%): Step 1 - 81.0 g (0.5 mol) of 4-acetoxystyrene, 30.47 g (0.215 mol) of tert-butyl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried under vacuum at 50° C. to produce a white powder (Mw=14,500 and Mw / Mn=2.25). Step 2 - 10 grams of the copolymer from step 1, 20 grams of ammonium hydroxide (28-30%) and 100 mL of methanol were heated at 65°C with stirring for 18 h. The resulting solution was precipitated in 500 mL of HCl solution (5%). After stirring for 30 min, the resulting powder was filtered. Rinse with 150 mL of water and dry under vacuum at 50°C to provide a white powder (Mw = 12,500 and Mw / Mn = 2.05).
[0096] Example 12: Synthesis of Copolymer B4
[0097] Poly(4-hydroxystyrene-co-tert-butyl methacrylate-co-2-methyl-2-adamantyl methacrylate) (70 / 20 / 10, molar ratio) (aromatic group content: 70 mol%): Step 1 - 60.75 g (0.375 mol) of 4-acetoxystyrene, 15.2 g (0.107 mol) of tert-butyl methacrylate, 12.54 g (0.054 mol) of 2-methyl-2-adamantyl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water with stirring. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried under vacuum at 50° C. to produce a white powder (Mw=14,900 and Mw / Mn=2.13). Step 2 - 10 grams of the copolymer from step 1, 20 grams of ammonium hydroxide (28-30%) and 100 mL of methanol were heated at 65° C. with stirring for 18 h. The resulting solution was precipitated in 500 mL of HCl solution (5%). After stirring for 30 min, the resulting powder was filtered. Rinse with 150 mL of water and dried under vacuum at 50° C. to provide a white powder (Mw=13,100 and Mw / Mn=2.05).
[0098] Example 13: Synthesis of Copolymer B5
[0099] Poly(4-hydroxystyrene-co-tert-butyl methacrylate-co-2-methyl-2-adamantyl methacrylate) (70 / 15 / 15, molar ratio) (aromatic group content: 70 mol%): Step 1 - 60.75 g (0.375 mol) of 4-acetoxystyrene, 11.43 g (0.08 mol) of tert-butyl methacrylate, 18.82 g (0.08 mol) of 2-methyl-2-adamantyl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water with stirring. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried under vacuum at 50° C. to produce a white powder (Mw=16,400 and Mw / Mn=2.34). Step 2 - 10 grams of the copolymer from step 1, 20 grams of ammonium hydroxide (28-30%) and 100 mL of methanol were heated at 65° C. with stirring for 18 h. The resulting solution was precipitated in 500 mL of HCl solution (5%). After stirring for 30 min, the resulting powder was filtered. Rinse with 150 mL of water and dried under vacuum at 50° C. to provide a white powder (Mw=14,000 and Mw / Mn=2.35).
[0100] Preparation of Photoresist Compositions (Comparative Photoresist Compositions and Photoresist Compositions of the Invention)
[0101] Four photoresist compositions were prepared and are referred to herein as photoresist compositions A2B3, A7B4, and A8B5, respectively.
[0102] Photoresist composition A2B3 includes 70 weight percent of copolymer A2 and 30 weight percent of copolymer B3, based on the total weight of copolymer A2 and copolymer B3.
[0103] Photoresist composition A7B4 includes 30 weight percent of copolymer A7 and 70 weight percent of copolymer B4, based on the total weight of copolymer A7 and copolymer B4.
[0104] Photoresist composition A8B5 includes 30 weight percent of copolymer A8 and 70 weight percent of copolymer B5, based on the total weight of copolymer A8 and copolymer B5.
[0105] In addition, each of the photoresist compositions A2B3, A7B4 and A8B5 was prepared as follows: a mixture of copolymer (A) and copolymer (B) was dissolved in an appropriate solvent (propylene glycol monomethyl ether acetate), and a quencher (tetramethyl ammonium hydroxide pentahydrate, 0.6 wt% of the total copolymer) and a surfactant (Silwet L7604, at 0.5 wt% of the total solids) were added to the resulting solution. The formulation of the control photoresist composition was the same except that only copolymer (B) was used instead of the mixture of copolymer (A) and copolymer (B).
[0106] The control photoresist compositions are referred to herein as photoresist compositions B3, B4 and B5. The control photoresist compositions were prepared by dissolving copolymer (B) in an appropriate solvent (propylene glycol monomethyl ether acetate) and adding PAG (triphenylsulfonium trifluorosulfonate, 5.0 wt % of the total copolymer), quencher (tetramethylammonium hydroxide pentahydrate, 0.6 wt % of the total copolymer) and surfactant (Silwet L7604, at 0.5 wt % of total solids) to the resulting solution.
[0107] All photoresist compositions were prepared at 20 wt% solids in an appropriate solvent (propylene glycol monomethyl ether acetate) and then filtered through a 0.2 μm filter.
[0108]
[0109] Lithography performance
[0110] The photoinduced solution was spin coated on a silicon wafer treated with an organic antireflective coating of 60 nm thickness. Coating was performed under standard solution spin coating to provide a film having a thickness of 1400 nm after soft baking at 130° C. for 60 seconds. The resulting film was exposed to a 0.53 numerical aperture KrF excimer laser stepper followed by a post-exposure bake at 110° C. for 60 seconds. The resulting film was developed using 0.263N tetramethylammonium hydroxide solution in double developer surface dwell mode (double puddle mode) for 40 seconds (20 / 20 second process).
[0111] A SEM CG6300 (HITACHI CD-SEM) instrument with the following parameters was used:
[0112] Accelerating voltage 800V Probe current 5.0pA Magnification 149997 Digital zoom 1 Frame rate 16 Image Rotation 0.0 degrees Optics high resolution Pixel 512,512 Automatic EF close Detector ratio 30% Detector Node SE+EF
[0113] The photoresist layers were patterned in a line and space pattern with a line width of 450 nm, and the patterned photoresist layers were analyzed on scanning electron microscope (SEM) images to evaluate their LWR (line width roughness) ( Figure 1 ).
[0114] Figure 1It is clearly shown that the photoresist composition of the present invention has a lower LWR than that of the comparative example.
[0115] Table 1 LWR of photoresist compositions A2, B3 and B3
[0116]
[0117] Table 2 LWR of photoresist compositions A7, B4 and B4
[0118]
[0119] Table 3 LWR of photoresist compositions A8, B5 and B5
[0120]
[0121] As can be seen from Tables 1-3 above, the photoresist compositions of the present invention achieve a % reduction in LWR of greater than 40%, preferably greater than 50%, and preferably greater than 60%, compared to the control photoresist composition.
[0122] While the invention has been described with respect to specific embodiments, the details thereof should not be construed as limiting, as it will be apparent that various embodiments, changes and modifications may be made without departing from the spirit and scope thereof, and it should be understood that such equivalent embodiments are intended to be included within the scope of the invention.
Claims
1. A composition comprising a mixture of two copolymers of copolymer (A) and copolymer (B), in: Copolymer (A) is an acetoxystyrene copolymer having a dissolution inhibiting acetoxy group, a pendant photoacid generator group and a photoacid dissociable group, wherein copolymer (A) contains equal to or greater than 60 mol%, preferably 70 mol% to 80 mol%, of an aromatic-containing group based on the total moles of the monomers; and Copolymer (B) is a hydroxystyrene copolymer having alkali-soluble hydroxyl groups and photoacid-dissociable groups, wherein copolymer (B) contains equal to or greater than 60 mol%, preferably 70 mol% to 80 mol%, of aromatic-containing groups based on the total moles of monomers.
2. The composition according to claim 1, wherein the content of copolymer (A) is in the range of 30 wt% to 70 wt%, and the content of copolymer (B) is preferably in the range of 30 wt% to 70 wt%, such as 30 wt%, 40 wt%, 50 wt%, 60 wt% and 70 wt%, based on the total weight of the mixture of the two copolymers of copolymer (A) and copolymer (B).
3. The composition according to any one of claims 1 to 2, wherein the aromatic-containing groups contained in copolymer (A) and copolymer (B) are selected from the group consisting of phenyl, biphenyl and naphthalene.
4. The composition according to any one of claims 1 to 3, wherein the photoacid dissociable groups contained in copolymer (A) and copolymer (B) are selected from the following: alkyl (meth)acrylate groups, alicyclic (meth)acrylate groups, or combinations thereof; Preferably, the photoacid-dissociable group is an alkyl (meth)acrylate group, wherein the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl; Preferably, the photoacid dissociable group is an alicyclic (meth)acrylate group selected from a 1-alkyl-1-cycloalkyl (meth)acrylate group and a 2-alkyl-2-adamantyl (meth)acrylate group; Preferably, the photoacid-dissociable group is a 1-alkyl-1-cycloalkyl (meth)acrylate group, wherein the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl; and the cycloalkyl group is selected from the group consisting of cyclopentyl, cyclohexyl and cycloheptyl; Preferably, the photoacid dissociable group is a 2-alkyl-2-adamantyl (meth)acrylate group, wherein the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl; Preferably, the photoacid-dissociable group is a combination of a 1-alkyl-1-cycloalkyl(meth)acrylate group and / or a 2-alkyl-2-adamantyl(meth)acrylate group and / or a tert-butyl(meth)acrylate group.
5. The composition according to any one of claims 1 to 4, wherein the side chain photoacid generator group contained in copolymer (A) is a 2,3,5,6-tetrafluoro-4-(methacryloyloxy)benzenesulfonic acid triphenylsulfonium group.
6. A composition according to any one of claims 1 to 5, wherein the weight average molecular weight (Mw) of copolymer (A) is 5,000-25,000 Daltons; and the polydispersity of copolymer (A) is 1.2-4.0; and wherein the weight average molecular weight (Mw) of copolymer (B) is 5,000-25,000 Daltons; and the polydispersity of copolymer (B) is 1.2-4.
0.
7. A chemically amplified positive photoresist composition comprising: (a) a mixture of two copolymers of copolymer (A) and copolymer (B), wherein copolymer (A) and copolymer (B) are defined in any one of claims 1 to 6; (b) a solvent or a mixture of solvents; (c) a base as a quencher; and (d) Optionally, a surfactant.
8. The chemically amplified positive photoresist composition according to claim 7, wherein the content of component (a) ranges from 5 wt% to 30 wt%; the content of component (b) ranges from 65 wt% to 95 wt%; and the content of component (c) ranges from 0.1 wt% to 5 wt%; and if present, the content of component (d) ranges from 0.1 wt% to 2.0 wt%, based on the total weight of the chemically amplified positive photoresist composition.
9. A process for producing the chemically amplified positive photoresist composition of any one of claims 7 to 8, comprising mixing each of components (a), (b), (c) and optionally (d).
10. Use of the chemically amplified positive photoresist composition according to any one of claims 7 to 8 for reducing line width roughness.
Citation Information
Patent Citations
Chemically amplified photoresist composition and process for its use
CN102472971A
Chemically amplified photoresist composition and process for its use
CN106980235A
Core-shell type hyper branched polymer, AMD resist composition
JP2008163057A
Chemically amplified positive photoresist composition for improving pattern profile
US20210216013A1
Core-shell-type hyperbranched polymer, resist composition, method for production of semiconductor device, and semiconductor device
WO2008081832A1
